The influence of promotion and service quality on customer satisfaction is mediated by the purchase decision at Pt Wijaya Karya Beton (Persero) Sales Area II - Saputra, Agus Adi; Helmi, Sulaiman; Fitriasuri; Mellita, Dina (Yayasan Sinergi Kawula Muda, 2025)
Companies in the construction sector are currently faced with an era of very fierce competition, the right marketing strategy is needed to increase market share. PT Wika Beton Sales Region II Palembang City as a large company is considered to have not maximized its performance in influencing the purchase decisions of its customers. This study aims to find out and analyze the influence of promotion and service quality on customer satisfaction mediated by purchase decisions. The research was conducted using a quantitative method through SEM-PLS analysis, sourced from a questionnaire distributed to 85 respondents. The respondents are customers of PT Wika Beton Sales Region II Palembang City who have made the least number of purchases. The results of the study are expected to reveal that the promotion program and the quality of service provided by the company can increase customer satisfaction in every purchase decision made. The expected influence is a significant positive influence, both partially and simultaneously. The results of this study are expected to be used as a reference for companies in formulating the most optimal marketing strategy in increasing sales in a sustainable manner.